MENINGKATKAN KUALITAS DAN PREFERENSI KONSUMEN TELUR ITIK DENGAN CARA MENURUNKAN LEVEL BAU AMIS TELUR ASIN YANG DIPERKAYA ANTIOKSIDAN DAUN JINTAN (Plectranthus amboinicus L SPRENG) - Ristina Siti Sundari; Andri Kusmayadi; Reny Hidayati; Adnan Arshad (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Food supply chain scarcity comes to the pinch and coerces us to make any food diversification for food security's sake. The eggs are one of the commodities to keep secure. Otherwise, the fish odor of duck egg often become caused by people less interest to consume duck egg. Instead, it has a higher nutrient composition than chicken as well. One of the alternate ways is Jintan leaf (Plectranthus amboinicus). Jintan leaf has the potency to eliminate odor sensory toward duck egg due to its bioflavonoid, phenol, volatile compound. This substance hypnotized could decrease and eliminate odor levels in duck egg. The research was carried out to know the most proper jintan leaf concentrations to eliminate salty duck egg odor. It used an explorative experimental method by Complete Block Design with three replication and continued by orthogonal contrast test to know which component is more prefer according to consumers. The odor of salty duck eggs decreased and began to decrease even at the 25-gram concentrate. Within the higher concentration, the higher decrease in odor sensory. For the economic aspect, we are not necessary to close in the highest concentration, but we suggest at the early odor sensory is disappeared, by 50 grams for 40 salty duck eggs. There is the other advance to further research, such as prolonging quality. This finding would be beneficial to producer and consumer and also researcher as the new variance of product.